2016
DOI: 10.11604/pamj.2016.24.176.9862
|View full text |Cite
|
Sign up to set email alerts
|

Chéilite tuberculeuse révélant une tuberculose pulmonaire

Abstract: La tuberculose de la cavité buccale reste rare. Elle admet un polymorphisme clinique et pose avant tout un problème de diagnostic. Nous rapportons le cas d'un homme de 42 ans présentant une chéilite tuberculeuse. L’intérêt de cette présentation est d’attirer l’attention sur la tuberculose que l’on peut retrouver de façon exceptionnelle dans certaines localisations, comme la lèvre buccale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Bhattacharya M. et al reported a child's GC second of pulmonary tuberculosis [5]. Other two authors described cheilitis as a secondary manifestation of latent pulmonary tuberculosis in adult patients in Cuba [6], respectively in Morocco [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhattacharya M. et al reported a child's GC second of pulmonary tuberculosis [5]. Other two authors described cheilitis as a secondary manifestation of latent pulmonary tuberculosis in adult patients in Cuba [6], respectively in Morocco [7].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the treatment of the LTBI is also under consideration, especially when the LTBI is displayed with distant lesions. In the reported association cases between GC and LTBI, the preferred treatment modality includes a combination of several anti-tubercular drugs (isoniazid, rifampicin, ethambutol and pyrazinamide) [4,5,6,7]. This is in contrast to the recommendations of WHO.…”
Section: Discussionmentioning
confidence: 99%
“…Bhattacharya M. et al reported a child with GC, described as tuberculid secondary to asymptomatic tuberculosis [6]. Other authors described also angular cheilitis as a secondary manifestation of asymptomatic tuberculosis in adult patients in Cuba [8] and Morocco [9].…”
Section: Discussionmentioning
confidence: 99%
“…In all reported cases of tuberculids associated with asymptomatic tuberculous infection and manifested as GC, the histological evaluation revealed both granulomatous inflammation and lack of MBT [5,6,8,9]. The underlying tuberculous infection was proved based on microbiological confirmation of MBT in sputum and radiography findings.…”
Section: Extensive Investigation For Underlying Tuberculosis In Addit...mentioning
confidence: 96%